2003
DOI: 10.1002/ijc.11397
|View full text |Cite
|
Sign up to set email alerts
|

Site‐specific human breast cancer (MDA‐MB‐231) metastases in nude rats: Model characterisation and in vivo effects of ibandronate on tumour growth

Abstract: Animal models are important tools to study the development of bone metastases and to evaluate strategies for their prevention and treatment. We here describe a new model in which tumour inoculation is achieved by injection of cancer cells into the femoral artery. This approach results in the development of multiple osteolytic lesions in the distal femora and proximal tibiae within 18 days after inoculation, with a success rate of 95-100% and no additional comorbidity. In untreated animals, osteolyses expanded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 25 publications
3
48
0
Order By: Relevance
“…Another study reported by Neudert at al. also pointed out that inoculation of breast cancer into femoral artery was able to stimulate multiple osteolytic lesions in the distal femoral and proximal tibiae within 18 days after inoculation, with a success rate of 95-100 % and no additional co morbidity 17 . Lastly, inoculation of tumor cells isolated from human suffer from breast cancer into mammary fat pad of nude mice was significantly induce breast cancer develop and metastasis to multiple mouse organs 18 Nevertheless, in the present study the tumor volume resulted from breast cancer inoculation in all groups were not similar (comparable) in size.…”
Section: Discussionmentioning
confidence: 97%
“…Another study reported by Neudert at al. also pointed out that inoculation of breast cancer into femoral artery was able to stimulate multiple osteolytic lesions in the distal femoral and proximal tibiae within 18 days after inoculation, with a success rate of 95-100 % and no additional co morbidity 17 . Lastly, inoculation of tumor cells isolated from human suffer from breast cancer into mammary fat pad of nude mice was significantly induce breast cancer develop and metastasis to multiple mouse organs 18 Nevertheless, in the present study the tumor volume resulted from breast cancer inoculation in all groups were not similar (comparable) in size.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, a model has been described that is characterized by site-specific osteolytic lesions after injection of MDA-MB-231 cells directly into the femoral artery of nude rats. 14 The disadvantage of this model is that the femoral artery has to be ligated, and spontaneous remission of lytic lesions occurred in up to 50% of animals at day 42 after tumor cell inoculation. In our model, the development of osteolytic lesions can be observed up to at least 110 days after tumor cell inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…(61) These models result in near 100% frequency of development of these ''experimental metastases'' and have been used to assess efficacy of therapeutic agents under development; such agents have been assessed, more specifically, for their ability to block breast cancer growth within the bone and breast cancer-mediated bone resorption. (62) They also have provided an in vivo system in which human cancer cells can be passaged through a bone microenvironment, aiding the development of breast cancer cells that have been selected for their osteotropism and thus reproducible and efficient osteotropic metastasis during subsequent rounds of growth in mice. Such cells can be used to study the genetic changes that are required for survival and proliferation of cancer cells within the bone environment, as well as the changes within the bone microenvironment induced by the disseminated cancer cells.…”
Section: Xenograft Models Of Breast Cancer Metastasismentioning
confidence: 99%